2019
DOI: 10.1186/s12864-019-5964-y
|View full text |Cite
|
Sign up to set email alerts
|

GWAS hints at pleiotropic roles for FLOWERING LOCUS T in flowering time and yield-related traits in canola

Abstract: Background Transition to flowering at the right time is critical for local adaptation and to maximize grain yield in crops. Canola is an important oilseed crop with extensive variation in flowering time among varieties. However, our understanding of underlying genes and their role in canola productivity is limited. Results We report our analyses of a diverse GWAS panel (300–368 accessions) of canola and identify SNPs that are significantly associated with variation in f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 72 publications
2
49
0
Order By: Relevance
“…These results are consistent with a previous study, which reported a multi-trait QTL (flanked by markers 3110489 and 3075574) for plant emergence, shoot biomass, flowering time, and seed yield mapped on chromosome A07 in the vicinity of the FT [30]. PRC2 is involved in trimethylation of histone H3 lysine 27 and regulates VERNALISATION INSENSTIVE 3 (VIN3) and plays an important role in epigenetic repression of FLC [35].…”
Section: Physical Mapping Of Significant Trait-marker Associationssupporting
confidence: 92%
See 2 more Smart Citations
“…These results are consistent with a previous study, which reported a multi-trait QTL (flanked by markers 3110489 and 3075574) for plant emergence, shoot biomass, flowering time, and seed yield mapped on chromosome A07 in the vicinity of the FT [30]. PRC2 is involved in trimethylation of histone H3 lysine 27 and regulates VERNALISATION INSENSTIVE 3 (VIN3) and plays an important role in epigenetic repression of FLC [35].…”
Section: Physical Mapping Of Significant Trait-marker Associationssupporting
confidence: 92%
“…This observed clustering of different QTL is consistent with genetic correlation among different traits in the RADH population (SupplementaryTable 1). In a previous study, Raman et al[30] found moderate to high genetic correlations for flowering time, early vigour, plant biomass and seed yield in an Australian DH population from Skipton/Ag-Spectrum//Skipton. Flowering time is an adaptive trait and shows pleiotropy with seed yield and other plant architectural traits in B. juncea and winter/spring crosses of B. napus[19,23,[30][31][32][33][34].…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Flowering time genetic pathways have been elucidated in Arabidopsis and most flowering time genes are known to be conserved between Arabidopsis and B. napus [21][22][23]. On this basis, many QTL and associated SNPs for flowering time have been detected in B. napus [24][25][26][27][28][29][30][31]. However, despite progress in understanding the genetic underpinnings of B. napus flowering time, a substantial proportion of flowering time variation remains to be explained.…”
Section: Introductionmentioning
confidence: 99%
“…However, the QTL LOD peaks identified here are distant from this location. Among the known flowering time genes on C2, FT (40), FLC (41) and FY (42) may have particularly substantial effects.FT has been implicated in B. napus flowering time divergence(28,43) and FLC has been found to explain ~23% of flowering time variation in B. napus(44). FY is a suppressor of the transcription factor FLC (42, 45), and lies in close physical proximity to the LOD peaks identified in this study.…”
mentioning
confidence: 65%